Trust Me, I’m a Pragmatist: A Partially Pragmatic Critique of Pragmatic Activism - Galperin, Joshua Ulan (Columbia Journal of Environmental Law, 2019)
Pragmatism is a robust philosophy, vernacular hand-waving, a method of judicial and administrative decisionmaking, and, more recently, justification for a certain type of political activism. While philosophical, judicial, and administrative pragmatism have garnered substantial attention and analysis from scholars, we have been much stingier with pragmatic activism—that which, in the spirit of the twenty-first century’s 140-character limit, I will call “pragtivism.” This Article is an introduction to pragtivism—environmental pragtivism in particular—a critique of the practice, and a constructive framework for addressing some of my critiques. As a central principle of their philosophy, pragmatists reject absolutes. Pragtivists, likewise, reject perfect environmental outcomes in deference to those that are, at least arguably, directionally correct. The idea of engaging private business is a more applied, but equally important principle. Pragmatists advocate that decisions are good if they work, if they are based on lessons from experience. Pragtivists believe that because engaging private businesses is a departure from their concept of “traditional” environmentalism, towards a path of less resistance, it is a superior process for environmental protection. As a vehicle to explore pragtivism, this Article uses the case of the Dunes Sagebrush Lizard: the deal between Texas and the U.S. Fish & Wildlife Service to prevent Endangered Species Act listing of the Lizard; the deficiencies of the Texas Conservation Plan that replaced the listing; the Environmental Defense Fund’s support of the Plan; and the D.C. Circuit’s eventual approval. If industry-led conservation in this vein is the future of environmentalism, how did we arrive at this point, and how can pragtivist organizations take care not to support decisions as facially flawed as this one? Finally, why do activists so love the word “pragmatic?” Is there a relationship between certain forms of environmental advocacy and pragmatic philosophy or do some use the word simply because of the good reputation it seems to have in society? This Article is a first attempt to answer some of these questions and to generate more analysis of the influence of pragmatism on environmental activism. Part II presents a novel typology of pragmatisms, describing the different ways that the philosophy has been applied both explicitly and implicitly by a number of important figures. Part III recounts the Dunes Sagebrush Lizard controversy in more detail to serve as a background on which to view more abstract issues of philosophy and activism. Part IV then attempts to unpack pragtivism, sketching a profile of pragtivism and placing it in contrast to “traditional” environmentalism both because the contrast is helpful in understanding pragtivism and because it is a large part of how pragtivists define themselves. In this same Part, I also offer my own critique of pragtivism, primarily in terms of its real-world application and effectiveness, explaining that it provides a weak basis for lasting environmental protection because it does not adequately consider public input, sufficiently learn from its own shortcomings, or fairly define itself or its alternatives, and at base, there is too little evidence of its positive environmental impacts. Finally, in Part V, I respond to my own critique and offer a constructive framework for decisionmaking that can partially rectify pragtivism’s weak points. That framework insists on attention to transparency, accountability, monitoring, large-scale impacts, precaution, good faith of partners, public participation, long-term strategy, and the signals that a pragtivist position might send. Although I hope the framework will make pragtivism more satisfying and effective, I am aware that some pragtivists may complain that I have offered too much of traditional environmental law. In a sense, I cannot contend with this likely challenge. But pragmatically, I am compelled to suggest that environmentalists advocate for more of what works, from experience, and less of what doesn’t.